Incrementor logic

你离开我真会死。 提交于 2019-11-26 18:52:22

Quoting Java Language Specification, 15.7 Evaluation Order:

The Java programming language guarantees that the operands of operators appear to be evaluated in a specific evaluation order, namely, from left to right.

The left-hand operand of a binary operator appears to be fully evaluated before any part of the right-hand operand is evaluated.

If the operator is a compound-assignment operator (§15.26.2), then evaluation of the left-hand operand includes both remembering the variable that the left-hand operand denotes and fetching and saving that variable's value for use in the implied binary operation.

So, essentially, i += ++i will remember the old value of i on the left side, before evaluating the right side.

Remember, evaluation order of operands and precedence of operators are two different things.

Showing evaluation order, step by step, with saved value in {braces}:

int i = 0;
i    = i    += (++i + (i    += 2 + --i) - ++i); // i = 0
i{0} = i    += (++i + (i    += 2 + --i) - ++i); // i = 0
i{0} = i{0} += (++i + (i    += 2 + --i) - ++i); // i = 0
i{0} = i{0} += (1   + (i    += 2 + --i) - ++i); // i = 1
i{0} = i{0} += (1   + (i{1} += 2 + --i) - ++i); // i = 1
i{0} = i{0} += (1   + (i{1} += 2 + 0  ) - ++i); // i = 0
i{0} = i{0} += (1   + (i{1} += 2      ) - ++i); // i = 0
i{0} = i{0} += (1   + 3                 - ++i); // i = 3
i{0} = i{0} += (4                       - ++i); // i = 3
i{0} = i{0} += (4                       - 4  ); // i = 4
i{0} = i{0} += 0                              ; // i = 4
i{0} = 0                                      ; // i = 0
0                                             ; // i = 0

Followup to edits to question

If we name the initial value I and the constant N:

int i = I;
i = i += (++i + (i += N + --i) - ++i);

Then we can see that the values are:

i{I} = i{I} += ((I+1) + (i{I+1} += N + I) - ((I+1+N+I)+1));
i{I} = i{I} += (I + 1 + (I + 1 + N + I) - (I + 1 + N + I + 1));
i{I} = i{I} += (I + 1 + I + 1 + N + I - I - 1 - N - I - 1);
i{I} = i{I} += I;
i{I} = I + I;
i = 2 * I;

This is the logic taking into account your first edit (with an unknown X):

public static void main(String[] args) {
    int i = 0;
    i = i+=(++i + (i+=X + --i) - ++i);
    // i = 0 += (++i + ((i += (X + --i)) - ++i));
    // i = 0 += (1 + ((i += (X + --i)) - ++i)); // i = 1
    // i = 0 += (1 + ((1 += (X + --i)) - ++i)); // i = 1 and i will then take the result of 1 += (X + --i)
    // i = 0 += (1 + ((1 += (X + 0)) - ++i)); // i = 0 and i will then take the result of 1 += (X + 0)
    // i = 0 += (1 + (X + 1 - ++i)); // i = X + 1
    // i = 0 += (1 + (X + 1 - X - 2)); // i = X + 2
    // i = 0 += (0); // i = X + 2
    // i = 0;
    System.out.println(i); // Prints 0
}

Tricks here:

For your second edit (with an unknown I added):

public static void main(String[] args) {
    int i = I;
    i = i+=(++i + (i+=X + --i) - ++i);
    // i = I += (++i + ((i += (X + --i)) - ++i));
    // i = I += (I+1 + ((i += (X + --i)) - ++i)); // i = I+1
    // i = I += (I+1 + ((I+1 += (X + --i)) - ++i)); // i = I+1 and i will then take the result of I+1 += (X + --i)
    // i = I += (I+1 + ((I+1 += (X + I)) - ++i)); // i = I and i will then take the result of I+1 += (X + I)
    // i = I += (I+1 + (X+2*I+1 - ++i)); // i = X + 2*I + 1
    // i = I += (I+1 + (X+2*I+1 - X-2*I-2)); // i = X + 2*I + 2
    // i = I += (I); // i = X + 2*I + 2
    // i = 2 * I;
    System.out.println(i); // Prints 2 * I
}

I suggest the following: format the code differently, so that there's only 1 statement per line, e.g.

@Test
public void test() {
    int i = 0;
    i = 
    i+=
    (
    ++i 
    + 
    (
    i+=
    2 
    + 
    --i
    ) 
    -
    ++i
    );
    System.out.println(i); // Prints 0 instead of 5
}

Then run it under the debugger and press F5 ("Step into") always. This will help you to understand in which order items get evaluated:

  1. int i=0;
  2. i=: ... (needs to wait for result of calculation A)
  3. i+= ... (needs to wait B)
  4. ++i: i=1
  5. i+= ... (needs to wait C)
  6. 2+
  7. --i: i=0
  8. ...: i=3 (result for wait C)
  9. -
  10. ++i: i=4 and operand of - is also 4
  11. ...: i=0 (result for wait B)
  12. ...: i=0 (result for wait A)

Line 10 will always make the result of line 3 0, so the initial value of i will never be changed by the whole operation.

Ok, let's break down every thing:

int i = 0; // i = 0, no big deal

Then starting into the most inner parenthesis:

(i+=2 + --i)
  • it first decrement i and use the result (-1)
  • then add 2 (-1+2=1)
  • and add the result to i (which is 0 at the start of the operation) (0+1=1=i)

At the end, the first decrement is ignored by the reassignation.

Next parenthesis:

i+= (++i + previous_result - ++i)
  • it increase the i ( with ++i) at two points
  • then the operation becomes (i+1) + previous_result - (i+2) (notice how the increment are not simultaneous) that gives 2 + 1 - 3 = 0.
  • the result of the operation is added to the initial i (0)

Again the increment will get discard by the reassignation.

finally:

i = previous_result

Which gives 0 :)

I traced the value of i and here are the results:

i = i+=(++i + (i+=2 + --i) - ++i);
initialization: i = 0;
++i: i = 1;(1st one) and store this value
(i+=2 + --i): In it
 --i: i = 0;(i was changed by the previous ++i)
 i += 2 + 0: i = 2;(value of the inner (i+=2 + --i), store it)
++i: i = 3;
1 + 2 -3: i = 0;
i += 0: i = 0;

The value of the 2nd i from the left is not zero, it is the value of i after all the operations to the right are finished.

Because of the highest precedence (...) will be evaluated first then ++ & -- and then remaining operators. Your expression is like

i = i += ( (++i) + (i+=2 + (--i)) - (++i) );

//i = i = i + ( (++i) + (i+=2 + (--i)) - (++i) );
//i = i = 0 + ( (++i) + (i+=2 + (--i)) - (++i) );
//i = i = 0 + ( (1) + (i+=2 + (--i)) - (++i) );
//i = i = 0 + ( (1) + (i+=2 + (0)) - (++i) );
//i = i = 0 + ( (1) + (2 + (0)) - (++i) );
//i = i = 0 + ( (1) + (2) - (++i) );
//i = i = 0 + ( (1) + (2) - (3) );
//i = i = 0 + ( 3 - 3 );
//i = i = 0 + ( 0 );
//i = 0

Please fully parenthesize your expression. You will understand evaluation order of expression.

For your EDIT 1

i = i+=( (++i) + (i+=32500 + (--i) ) - (++i) ); 

// 0 + ( (++i) + (i+=32500 + (--i) ) - (++i) ); // i = 0
// 0 + ( (1) + (i+=32500 + (--i) ) - (++i) );  // i = 1
// 0 + ( (1) + (i+=32500 + (0) ) - (++i) ); // i = 0
// 0 + ( (1) + (32500 + (0) ) - (++i) );  // i = 32500
// 0 + ( (1) + (32500) - (++i) ); // i = 32500
// 0 + ( (1) + (32500) - (32501) ); // i = 32501
// 0 + ( 32501 - 32501 ); // i = 32501
// 0 // i = 0
Muthu

Paranthesis takes the precedence. order would be from inner most to outermost

(i+=2 + --i) =>i=i+=2==(2) --2 =0 
(++i - ++i)  =>1-1=0 
i=i+ =0+0 =0

Each expression evaluates to 0

易学教程内所有资源均来自网络或用户发布的内容,如有违反法律规定的内容欢迎反馈
该文章没有解决你所遇到的问题?点击提问,说说你的问题,让更多的人一起探讨吧!